2000
DOI: 10.1289/ehp.00108553
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical-activated luciferase gene expression bioassay and gas chromatography for PCB determination in human serum and follicular fluid.

Abstract: We assessed exposure to dioxin-like compounds using chemical and bioassay analysis in different matrices in a female population. A total of 106 serum and 9 follicular fluid samples were collected from infertile women attending Centers for Reproductive Medicine in Belgium from 1996 to 1998. Major polychlorinated biphenyl (PCB) congeners were quantified by chemical analysis using gas chromatography with electron-capture detection, and the chemical-activated luciferase gene expression (CALUX) bioassay was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 29 publications
3
25
1
Order By: Relevance
“…Thus, there is no basis for assigning the approximate 700-fold difference between analytical TEQ and bioassay IEQ observed in this study, to possible synergism. Moreover, it has previously been demonstrated that when assessing purified fractions of PCDD/Fs and PCBs, the TEQ values determined using bioassays similar to the one used in the current study generally agree with those determined using HR-GC/MS analysis (Pauwels et al, 2000;Koppen et al, 2001;Covaci et al, 2002;Warner et al, 2005). It is more likely that the major portion of the activity measured in the reporter gene bioassay of whole blood is from non-PCDD/F or PCB AHR agonists present in the minimally purified extracts.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, there is no basis for assigning the approximate 700-fold difference between analytical TEQ and bioassay IEQ observed in this study, to possible synergism. Moreover, it has previously been demonstrated that when assessing purified fractions of PCDD/Fs and PCBs, the TEQ values determined using bioassays similar to the one used in the current study generally agree with those determined using HR-GC/MS analysis (Pauwels et al, 2000;Koppen et al, 2001;Covaci et al, 2002;Warner et al, 2005). It is more likely that the major portion of the activity measured in the reporter gene bioassay of whole blood is from non-PCDD/F or PCB AHR agonists present in the minimally purified extracts.…”
Section: Discussionsupporting
confidence: 78%
“…More recently, the use of in vitro bioassays based on AHR-regulated genes has increased for estimating HAH concentrations in environmental media, for example, US EPA Method 4425 (Hu et al, 1995;Giesy et al, 1997;Pauwels et al, 2000;US EPA, 2000;Koppen et al, 2001;Covaci et al, 2002;Denison et al, 2004). A commonly used commercially available cell bioassay is the chemical-activated luciferase gene expression (CALUX) bioassay that measures the ability of a chemical mixture to activate AHR-dependent gene expression of the firefly luciferase gene in genetically modified cell lines relative to activation by TCDD (Aarts et al, 1995;Garrison et al, 1996;Murk et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using the CALUX s by BDS bioassay all report using 1-4 ml serum (Pauwels et al, 2000;Koppen et al, 2001Koppen et al, , 2002. However, in this study, using 2 ml of plasma per replicate analysis for the CALUX s by XDS bioassay, 31% of samples were not detectable for the PCDD/PCDF fraction and 94% of the samples were not detectable for the PCB fraction.…”
Section: Discussionmentioning
confidence: 59%
“…The CALUX s by BDS bioassay has been used to estimate serum TEQ in epidemiologic studies of endometriosis (Pauwels et al, 2001), immunologic markers (Van Den Heuvel et al, 2002), and sexual maturation Nawrot et al, 2002). However, limited comparison studies of the CALUX s by BDS bioassay with the chemical analysis measurements have been completed (Pauwels et al, 2000;Koppen et al, 2001). Two studies have been completed comparing the CALUX s by XDS bioassay with HRGC/ HRMS data (Kayama et al, 2001(Kayama et al, , 2002Van Wouwe et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation